Penyidikan Tindak Pidana yang Berkaitan dengan Homoseksualitas di Deli Serdang: Tantangan Hukum dan Upaya Penegakan Hukum - Fajar Prayogi; Ramadani Ramadani (Verdict: Journal of Law Science, 2026)
The investigation of criminal cases related to same-sex conduct presents legal and evidentiary challenges due to the sensitive nature of the cases, the private circumstances in which incidents may occur, and the social stigma surrounding homosexuality. These conditions may affect the availability of witnesses and other evidence required for criminal proceedings. This study aims to examine the implementation of investigations, identify evidentiary obstacles, and analyze the efforts undertaken by investigators in handling criminal cases related to same-sex conduct within the jurisdiction of Deli Serdang Resort Police. This study employs an empirical juridical method using case and statutory approaches. Primary data were obtained through field observations and interviews with the Criminal Investigation Unit of Deli Serdang Resort Police, while secondary data were collected through legal and literature research. The data were analyzed qualitatively and descriptively. The findings indicate that investigations are conducted based on concrete criminal acts rather than sexual orientation. The principal obstacles involve limited direct witnesses, the private nature of incidents, reluctance of victims or witnesses to provide information due to shame and social stigma, and limited evidence. Investigators address these challenges by optimizing witness and victim examinations and utilizing expert testimony, visum et repertum, physical evidence, electronic evidence, and digital forensics when necessary. Strengthening investigators’ capacity in handling sensitive cases, particularly in evidence assessment, digital forensics, and victim- and witness-sensitive investigation procedures, is recommended to ensure lawful, objective, and accountable enforcement.